The Impact of Organizational Socialization and Career Development on Intention to Change Work in Public Companies in Pakistan - Purnomo, Singgih; Utami, Indah Wahyu; Gill, Atif Ali (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This study aims to discuss the impact of socialization about organizational goals and career development on intention to change jobs with coaching and career development as a moderating role.Design/Methodology/Approach: This research data were obtained from public companies involved in providing products and services to their customers. There were 400 respondents selected to be given a questionnaire that included closed questions, and 378 questionnaires were selected for further analysis. The sampling technique used was purposive sampling. Both differentiation and regression studies were employed in evaluating the relationship between the independent and dependent variables by SPSS software.Research findings: The results of this study revealed that there was a positive relationship between organizational socialization and career development. Besides, it was also found that there was a negative relationship between the purpose of structural socialization and the intention of changing jobs. Theoretical contribution/Originality: The moderating role of coaching and employee progress strengthens the relationship between organizational socialization and career development. This study uncovered that the organizational socialization component was closely related and consistently increased employee loyalty.Practitioner/Policy implication: The results of this study are good news for managers because the board of directors has a very significant role in socializing the organization.Research limitation/Implication: The scope of this research itself is relative and insignificant due to the limited number of samples. Thus, expanding the sample size and adding a wider area will be able to strengthen the results of this study. New research should be designed to investigate various career development programs that can increase employee loyalty so that it is not easy to change jobs. Organizational managers are also encouraged to innovate in creating and supporting employee career development, especially for novice employees, by providing various experiences to facilitate their career development.